Home Price Expectations and Spending: Evidence from a Field Experiment - Felix Chopra; Christopher Roth; Johannes Wohlfart (Center for Economic Studies and ifo Institute (CESifo), 2023)
How do households adjust their spending behavior in response to changes in home price expectations? We conduct a field experiment with a sample of Americans that links survey data on home price expectations to actual spending behaviour as measured in a rich home-scanner dataset. In the experiment we exogenously vary households' home price expectations by providing them with different expert forecasts. Homeowners do not adjust their spending in response to exogenously higher home price expectations, consistent with wealth effects and higher expected housing costs offsetting each other. However, renters reduce their spending in response to an increase in home price expectations. We provide evidence that the effects on renters operate through an increase in expected rental costs and higher expected costs of a future home that many renters intend to buy. Our evidence has implications for the role of asset price expectations in business cycle dynamics and consumption inequality.
Keywords: D14; D83; D84; E03; E21; 330; consumption; expectations; home prices; homeowner; information; renter